Mixing enhancement of the multi hydrogen fuel jets by the backward step. (15th July 2020) - Peng, Yeping; Barzegar Gerdroodbary, M.; Sheikholeslami, M.; Shafee, Ahmad; Babazadeh, Houman; Moradi, R.
Abstract: For the improvement of the present high-speed vehicles, fuel mixing is the significant process in the combustor. Current article employed numerical tools to scrutinize the role of the upstream step condition on the mixing efficiency of the multi hydrogen jets within the scramjet. This work tries to disclose the impact of the free-stream Mach and multi-jet arrangements on the feature of the fuel jets. Besides, the fuel mixing efficiency of the step condition is studied in the downstream of the jets. To do this, a three-dimensional model is considered to ensure that the real physics of the problem associated with hydrogen jets and freestream is considered. To solve the problem, RANS equations are chosen, and the SST approach is selected for the calculation of the viscosity in high-speed flow. The fuel jet has been injected within four multi sonic injectors and the free stream Mach number (Ma) is within 3–4. The computational simulations show that the impact of the step condition declines as the free-stream Ma is increased. Besides, the impact of the step on the fuel mixing enhances when the pressure ratio of the jets declines. Our findings show that fuel mixing in region of the fuel injection declines as the jet space increases from 4 Dj to 10 Dj while the downstream mixing efficiency enhances up to 28%.